Analysis of the Impact of Covid- Analysis of the Impact of Covid-19 on Sales Volume, Revenue, Income (Case Study of Vegetable Traders at Angso Duo Market, Jambi): Analysis of the Impact of Covid-19 on Sales Volume, Revenue, Income (Case Study of Vegetable Traders at Angso Dua Market, Jambi) - Winarni, Etik; Eka Putra, Iwan; Tamtomo, Hario; Arif, Muhammad (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This study aims to analyze the impact of Covid-19 on the volume of vegetables, revenue, and income traded by traders before and during Covid-19 at the Angso Duo Market Jambi. The data analyzed using the paired t-test analysis generally examines the difference between two observations. This kind of test is carried out on the subject being tested for the situation before and before the process, or the subject of a similar (similar) pair. Paired t-test in this study, will test whether there are significant differences in the observed variables at the beginning of the observation period and the end of the observation period. The basis for decision making is if the significance level > 0.05, then Ho is accepted, if the significance is <0.05 then Ha is accepted. From the results of the analysis and research discussion From the results of the analysis and discussion of research, the average sales volume of vegetables before Covid-19 was 224,235kg/month and during Covid-19 the volume was 131,285kg/month. This shows that there is a real and significant difference in the volume of vegetable sales before and during Covid-19 at the Angso Duo Jambi Market. Meanwhile, the average vegetable sales revenue before Covid-19 was IDR 68,045,977.01 and during Covid-19 it was IDR 34,816,091.95. This shows that there is a real and significant difference in vegetable receipts before and during Covid-19 at the Angso Duo Jambi Market. And the average vegetable sales income before Covid-19 was IDR 20,452,873.56 and during Covid-19 the income was IDR 72,990,804.59. This shows that there is a real and significant difference in vegetable receipts before and during Covid-19 at the Angso Duo Jambi Main Market.